IGFRI-CIAT collaboration – Planning meeting 15-17th January 2020 - Atieno, Mary Otieno; Douxchamps, Sabine; Cardoso Arango, Juan Andrés; Peters, Michael (Bioversity International and the International Center for Tropical Agriculture, 2020)
In the frame of the preparations of the ICAR-Alliance of Bioversity and CIAT collaborative workplan 2020-2025, a planning meeting was held at the Indian Grassland and Fodder Institute (IGFRI) in Jhansi, India, from 15-17th January, 2020. In attendance were IGFRI scientists led by their Director – Dr Vijay Kumar and the Tropical Forages Program team leader Dr. Michael Peters, the Asia Tropical Forages lead Dr. Sabine Douxchamps as well as representatives from the team Drs. Juan Andres Cardoso and Mary Atieno. The main objective was to refine potential areas of collaboration and develop an activity plan. The team also visited on-station trials in Jhansi.